Industry 4.0 and Marketing: Towards an Integrated Future Research Agenda - Rosário, Albérico Travassos; Dias, Joana Carmo (Journal of sensor and actuator networks, 2022)
Industry 4.0, or the Fourth Industrial Revolution, is driven by innovative technologies that have profound effects on both production systems and business models. This revolution is characterized by the addition of disruptive technologies and methods. These aspects of Industry 4.0 have a significant impact on marketing, and have led to an evolution to ensure that marketing activities align with technological advancements and address consumers’ current needs. The purpose of this paper is to formulate and discuss future research avenues for marketing considering the changes brought about by Industry 4.0. The approach taken in the paper is to review the relevant literature and focus on the key themes which are most important for future research on Industry 4.0 and marketing. Therefore, a Systematic Bibliometric Literature Review was conducted based on the SCOPUS indexing online database of scientific articles, the most important peer-reviewed journal database in the academic world. The paper finds that there are a number of research avenues for marketing researchers to conduct investigations in, but the most important areas are five marketing principles in Industry 4.0: cooperation, conversation, co-creation, cognitivity, and connectivity. Future research should focus on the quantitative study of these five principles.